A systematic model improves hepatitis C virus birth cohort screening in hospital‐based primary care. Issue 6 (23rd January 2017) - Goel, A.; Sanchez, J.; Paulino, L.; Feuille, C.; Arend, J.; Shah, B.; Dieterich, D.; Perumalswami, P. V.
Summary: Despite national and local governing board recommendations in the United States of America to perform an HCV screening test in baby boomers, screening rates remain low. Our goal was to study the impact of an HCV screening and link‐to‐care programme with patient navigation in two New York City primary care practices. This was a 2‐year prospective study of patients born between 1945‐1965 ("baby boomers") with encounters at two primary care practices at the Mount Sinai Hospital between November 1, 2013 and November 30, 2015. Baseline HCV screening rates were collected for four months. A multifaceted intervention was sequentially implemented involving electronic alerts, housestaff education, data feedback and patient navigation. HCV screening rates and link to care, defined as attending an appointment with a viral hepatitis specialist, were compared before and after these interventions. There were 14 642 primary care baby boomer patients of which 4419 (30.2%) were newly screened during the study. There was a significant increase in HCV screening rates from 55% to 75% ( P <.01) with an HCV seropositive rate of 3.3%. Factors associated with being HCV seropositive included older age ( P <.01), male sex ( P <.01), African American race ( P <.01) and receiving care in the housestaff practice ( P <.01). With patient navigation, 78 of 84 (93%) newly diagnosed HCV‐infected persons were referred to a specialist and 60 (77%) attended their first appointment. A structured, multifaceted HCV screening programme using well‐studied principles identifies a large number of undiagnosed baby boomers within hospital‐based primary care and improves access to specialty providers in a timely manner.